2016
DOI: 10.1111/nyas.13080
|View full text |Cite
|
Sign up to set email alerts
|

Airway reflux

Abstract: An ever-increasing number of adult and pediatric disorders have been shown to be influenced or caused by airway reflux. This has become a controversial and complicated aspect of medicine that requires a multidisciplinary approach. Evidence indicates that it is not only the acidic components of gastric refluxate that injure extraesophageal tissues but also the nonacidic components, such as pepsin and bile. There is a realization that proton pump inhibitors will not be effective when nonacidic components of refl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 54 publications
(114 reference statements)
0
42
0
1
Order By: Relevance
“…In that respect, some new noninvasive diagnostic approaches have been developed, such as pepsin detection in saliva samples (Peptest, RD Biomed, Milan, Italy) . This approach was developed according to some studies, which reported that the deposit of pepsin on the laryngopharyngeal mucosa leads to the development of mucosal inflammation and injury and the related symptoms and signs . Peptest (RD Biomed) provides a measurement of the pepsin saliva concentration, which theoretically is correlated with the occurrence of pharyngeal/proximal esophageal reflux episodes within the previous hours .…”
Section: Introductionmentioning
confidence: 99%
“…In that respect, some new noninvasive diagnostic approaches have been developed, such as pepsin detection in saliva samples (Peptest, RD Biomed, Milan, Italy) . This approach was developed according to some studies, which reported that the deposit of pepsin on the laryngopharyngeal mucosa leads to the development of mucosal inflammation and injury and the related symptoms and signs . Peptest (RD Biomed) provides a measurement of the pepsin saliva concentration, which theoretically is correlated with the occurrence of pharyngeal/proximal esophageal reflux episodes within the previous hours .…”
Section: Introductionmentioning
confidence: 99%
“…Vaezi suggested that when treating patients with LPR using a proton pump inhibitor (PPI), treatment should not be preceded by pH monitoring . Recently combined multichannel intraluminal impedance (MII) and pH monitoring (MII–pH) has provided an advance in LPR diagnostics; however, the procedure is still too invasive to be a convenient tool for screening LPR in clinics …”
Section: Introductionmentioning
confidence: 99%
“…5,6 Recently combined multichannel intraluminal impedance (MII) and pH monitoring (MII-pH) has provided an advance in LPR diagnostics; however, the procedure is still too invasive to be a convenient tool for screening LPR in clinics. 7 Based upon a careful study of pH monitoring used to confirm LPR cases, Belafsky et al 8 Symptom Index (RSI), a self-administered nine-item questionnaire that helps physicians assess the severity of a patient's LPR symptoms both before and after treatment. According to their article, patients with an RSI score ≥13 were considered to be potential LPR sufferers.…”
Section: Introductionmentioning
confidence: 99%
“…Laparoscopic Nissen fundoplication is usually reserved for patients with no response to the above treatment options (46). Neuromodulation with amitriptyline or gabapentin has demonstrated success in modifying the cough response in adults (47). …”
Section: Pediatric Gastroenterologist Perspectivementioning
confidence: 99%